Novel Immunohistochemical and Morphological Approaches in a Retrospective Study of Post-Mortem Myocarditis - Oana Neagu; Violeta Chirică; Lăcrămioara Luca; Maria Bosa; Alina Tița; Mihail Constantin Ceaușu (Medicina, 2024)
Background and Objectives: This study presents a retrospective analysis of 26 autopsy cases from a single centre, primarily focusing on forensic cases, with a majority of male individuals. Materials and Methods: We systematically analysed autopsy reports and cardiac tissue slides using haematoxylin-eosin stain and immunohistochemistry for CD3, CD163, and IL-6. The histological assessment evaluated key variables such as inflammation severity, necrosis, and background changes using a standardised grading system. Quantitative analysis of immunohistochemical markers was performed, calculating the percentage of positively stained cells within the inflammatory infiltrate. Results: The average age was 51.6 years, slightly skewed towards older males. The fatalities varied widely, with sudden death and drug abuse being the most common conditions linked to myocarditis findings on histological examination. A strong correlation was found between the severity of inflammation (measured by size within a myocardium section) and the scoring system based on the number of inflammatory foci per section (p ≤ 0.001). Most cases showed mild to minimal fibrosis, with some exhibiting moderate to severe fibrosis, arteriosclerosis, and myocyte hypertrophy. The presence of protein CD3 in the inflammatory infiltrate revealed a moderate inverse correlation between the CD3 values and the severity of inflammation and necrosis, and a strong inverse correlation with neutrophil levels. CD3 levels were higher in sudden death cases and lower in cases with numerous inflammatory foci, highlighting the discreet nature of lymphocytic myocarditis. Macrophage presence, assessed using CD163, showed a moderate inverse correlation with neutrophil levels and significant differences between sudden death and non-sudden death cases. Macrophage-rich inflammation was observed in cases with pneumonia/bronchopneumonia-associated lesions. IL-6 expression showed a moderate direct correlation with inflammation severity (p = 0.028), severity of necrosis (p = 0.005), and the number of inflammatory foci per section (p = 0.047). A moderate inverse correlation was found between CD3 and IL-6 expression (p = 0.005). Conclusions: These findings highlight the need for a unique immunohistochemical approach in forensic cases of myocarditis, differing from guidelines for endomyocardial biopsies due to diverse inflammatory cells. The study suggests exploring inflammatory chemokines within myocarditis foci for their significance in clinical scenarios. Specifically, IL-6, a crucial pro-inflammatory interleukin, correlated significantly with the severity of inflammation and necrosis (p < 0.05). This study provides novel and valuable insights into the histopathological and immunological markers of myocarditis in autopsy cases.